The Tribes of Zambia - Brelsford, W.V. (The Government Printer, Lusaka, 1956)
In 1934, the late J. Moffat Thomson, C.B.E., then Secretary for Native Affairs, wrote a Memorandum on the Native Tribes and tribal Areas of Northern Rhodesia. The tribal map which accompanied the Memorandum was drawn by the late W. C. Fairweather, C.B.E., then Director of Surveys. This .Memorandum, printed by the Government Printer, has long been out of print and there has been no handy guide to the tribes of the Territory. On the other hand, there has been so much research and so many writings on the tribes during the past twenty years that a reprinting of Moffat Thomson's work would Dot have been sufficient to indicate the present knowledge of tribal origins and history. This work then is completely new. I have quoted freely from Moffat Thomsor because his paper was the first comprehensive description of where our tribes came from and their relationships with each other. It formed an invaluable basis for future research. But his paper was very short and I have had to enlarge considerably in order to make full use of later studies. I have not hesitated to contradict Moffat Thomson on occasion and, in order to make this work as authoritative as possible, I have quoted extensively from acknowledged experts. At the same time, I have tried to keep the descriptions simple and straightforward and I have avoided, I hope, any ethnological theorising. The result is, no doubt, uneven. The amount of space given to a tribe does not necessarily indicate its relative importance. There may have been more written about it or, as in the case of many of the smaller tribes, it may be of more interest to write about them before they are absorbed by larger units. In any case most of the larger units, e.g. Bemba, Ngoni, Lozi, have a full-scale bibliography of their own. Research, especially under the aegis of the Rhodes-Livingstone Institute, still goes on and knowledge of tribal origins and affinities is constantly being extended, so that this work is far from being exhaustive and does not pretend to be anything but a quick survey of tribal origins as known to-day. Criticism has been made of the « rather miscellaneous scraps of ethnographic data that keep popping up here and there" in this book. It is true that the theme of this work is historical rather than sociological, but the. scraps", e.g. on the Tonga or Mambwe, do tie up with the recent history and development of the tribe concerned. They also add interest, I believe, and emphasise differences in cultural history.
Heritage
Keywords: Native Tribes; Zambia; Tribes